БЕЗДАВАЧЕВЕ КЕРУВАННЯ КУТОВОЮ ШВИДКІСТЮ ДВИГУНІВ ПОСТІЙНОГО СТРУМУ НА ОСНОВІ НАТУРАЛЬНИХ ВЛАСТИВОСТЕЙ СТІЙКОСТІ - Пересада, С.М.; Ніконенко, Є.О.; Панченко, О.Я.; Строєвий, С.О. (Інститут електродинаміки Національної академії наук України, 2025)
In this paper, a speed control system for permanent magnet DC motor is designed which does not require an angular speed sensor. It guarantees asymptotic tracking of the reference angular speed trajectories under the action of a constant unknown load torque. The control algorithm is based on information about the motor armature current and is characterized by the fact that it does not include an angular speed observer. It simplifies the control system implementation and configuration, and reduces the control system complexity. The closed-loop system analysis shows that for controller gains tuning, the well-known settings can be applied to the resulting structure, which include binomial distribution, as well as “symmetric” optimum and “modular” optimum. The resulting closed-loop system has robustness properties with respect to coordinate disturbances and can be effectively used in applications with low and medium control quality requirements. Ref. 9, fig. 5.